Introduction to Social Psychology : A European Perspective - Edited by Hewstone, Miles and Stroebe, Wolfgang (Malden, Mass. Blackwell Publishing, 2004)
In this third edition, Hewstone and Stroebe have brought together some of the key theorists of European social psychology to produce an authoritative introduction to social psychology. The book includes new chapters on health psychology, organizational psychology and cooperation and conflict
Include Illustration and Index
Keywords: Social psychology -- Europe